2009
DOI: 10.1093/pasj/61.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nonlinear Evolution of Baryon Acoustic Oscillations: Convergence Regime of $N$-body Simulations and Analytic Models

Abstract: We use a series of cosmological N-body simulations and various analytic models to study the evolution of the matter power spectrum in real space in a Λ Cold Dark Matter universe. We compare the results of N-body simulations against three analytical model predictions; standard perturbation theory, renormalized perturbation theory, and the closure approximation. We include the effects from finite simulation box size in the comparison. We determine the values of the maximum wavenumbers, k lim 1% and k lim 3% , be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 64 publications
5
133
0
Order By: Relevance
“…3 yields a 3-halo contribution that decays significantly faster at high k. At z = 0.35 and z = 1, two numerical points in the range 0.1 < k < 0.2 h Mpc −1 suggest that this may be a true improvement on these quasilinear scales. This improvement might be important for the analysis of baryon acoustic oscillations; it has been shown that resummation schemes give better predictions for the power spectrum on this scale (e.g., Nishimichi et al 2009;Valageas & Nishimichi 2011), and we could expect the same thing for the bispectrum. However, beyond 0.2 h Mpc −1 the faster decay significantly worsens the agreement with the simulations.…”
Section: Dependence On the Perturbative Schemementioning
confidence: 85%
“…3 yields a 3-halo contribution that decays significantly faster at high k. At z = 0.35 and z = 1, two numerical points in the range 0.1 < k < 0.2 h Mpc −1 suggest that this may be a true improvement on these quasilinear scales. This improvement might be important for the analysis of baryon acoustic oscillations; it has been shown that resummation schemes give better predictions for the power spectrum on this scale (e.g., Nishimichi et al 2009;Valageas & Nishimichi 2011), and we could expect the same thing for the bispectrum. However, beyond 0.2 h Mpc −1 the faster decay significantly worsens the agreement with the simulations.…”
Section: Dependence On the Perturbative Schemementioning
confidence: 85%
“…We determine this validity regime of the perturbation theory by solving the equation 17) for k, where P lin is the linear power spectrum. This limit of k represents the range of the 1%-level accuracy, which has been empirically found by comparisons between the perturbation theory predictions and N-body simulations [38]. Of course, this condition was calibrated in simulations in GR and there is no guarantee that this condition can be applied to modified gravity models, but this limit gives an useful indication of the validity of the perturbations theory.…”
Section: Quasi Non-linear Power Spectramentioning
confidence: 95%
“…(The benefit of these terms has already been shown in studies of the 3D matter density power spectrum, especially for the accurate prediction of the baryon acoustic oscillations, e.g. Jeong & Komatsu 2006;Nishimichi et al 2007Nishimichi et al , 2009Crocce & Scoccimarro 2008;Matsubara 2008;Taruya et al 2009;Sato & Matsubara 2011;Valageas & Nishimichi 2011a,b). In the weak-lensing context, this higher accuracy could also be useful for the analysis of future observations such as the Euclid mission (Refregier et al 2010).…”
Section: Convergence Power Spectrummentioning
confidence: 99%